Impact of acute versus repetitive moderate intensity endurance exercise on kidney injury markers. Issue 24 (21st December 2017) - Bongers, Coen C. W. G.; Alsady, Mohammad; Nijenhuis, Tom; Hartman, Yvonne A. W.; Eijsvogels, Thijs M. H.; Deen, Peter M. T.; Hopman, Maria T. E.
Abstract: Exercise may lead to kidney injury through several mechanisms. Urinary Kidney Injury Molecule‐1 (uKIM1) and Neutrophil Gelatinase‐Associated Lipocalin (uNGAL) are known biomarkers for acute kidney injury, but their response to repetitive exercise remains unknown. We examined the effects of a single versus repetitive bouts of exercise on markers for kidney injury in a middle‐aged population. Sixty subjects (aged 29–78 years, 50% male) were included and walked 30, 40 or 50 km for three consecutive days. At baseline and after exercise day 1 and 3, a urine sample was collected to determine uNGAL and uKIM1. Furthermore, urinary cystatin C, creatinine, and osmolality were used to correct for dehydration‐related changes in urinary concentration. Baseline uNGAL was 9.2 (5.2–14.7) ng/mL and increased to 20.7 (11.0–37.2) ng/mL and 14.2(8.0–26.3) ng/mL after day 1 and day 3, respectively, ( P ≤ 0.001). Baseline uKIM1 concentration was 2.6 (1.4–6.0) ng/mL and increased to 5.2 (2.4–9.1) ng/mL ( P = 0.002) after day 1, whereas uKIM1 was not different from baseline at day 3 (2.9 [1.4–6.4] ng/mL ( P = 0.52)). Furthermore, both uNGAL and uKIM1 levels were higher after day 1 compared to day 3 ( P < 0.01). When corrected for urinary cystatin C, creatinine, and osmolality, uNGAL demonstrated a similar response compared to the uncorrected data, whereas differences in uKIM1 between baseline, day 1 and day 3 ( P time = 0.63) were no longer observed for cystatin C and creatinine corrected data. A single bout of prolonged exercise significantly increased uNGAL concentration, whereas no changes in uKIM1 were found. Repetitive bouts of exercise show that there is no cumulative effect of kidney injury markers. Abstract : We examined the effects of a single versus repetitive bouts of exercise on markers for kidney injury in a middle‐aged population. A single bout of prolonged exercise significantly increased uNGAL concentration, whereas no changes in uKIM1 were found. Repetitive bouts of exercise show that there is no cumulative effect of kidney injury markers.